Unravelling the structure of riboflavin synthase from Leptospira kmetyi for designing potential anti-bacterial drug - Mohamad Aris, Sayangku Nor Ariati (2021)
In Malaysia, an increasing number of reported cases of leptospirosis had resulted in significant number of deaths over the past decade. The leptospirosis disease is caused by a bacterial pathogen, Leptospira sp. that contaminates soil and water. Like other microorganisms, Leptospira sp. have absolute dependency on riboflavin biosynthetic pathway for riboflavin supply. Therefore, targeting this pathway is a potential strategy for treating diseases caused by this kind of pathogen to develop novel and safe antimicrobial agents. In this study, riboflavin synthase from Leptospira kmetyi, a local isolate of the pathogen was chosen as a potential drug target as it is an important enzyme catalyzing the last step of riboflavin biosynthesis. To date, there is no crystal structure of riboflavin synthase from Leptospira sp. Therefore, the aim of this study is to unravel the crystal structure of the riboflavin synthase from L. kmetyi for designing of antibacterial drugs against Gram-negative bacteria. To begin, a computational approach was used in order to identify potential lead compounds that inhibit druggable riboflavin synthase and to determine the stability of the selected inhibitors. Homology modelling was performed using the riboflavin synthase (1I8D) from E. coli as a template, where the modelled structure showed a homotrimer of 23 kDa subunits, with three active sites of the trimer identified have to lie a between pair of monomers. In the virtual screening experiment, approximately 1,000,000 commercial drug compounds from the ZINC database were screened to find the best lead. The potential lead compound with the highest docking score (-10.987 Kcal/mol) was identified to be ZINC21883831 which is 2-[(2-chloro-4-fluoro-phenyl) methylsulfanyl]-7-phenyl-3,5-dihydropyrrolo-[2,3-]pyrimidin-4-one. Subsequently, molecular dynamic simulation trajectories were evaluated for 60 ns for stability parameters including root mean square deviation (RMSD), root mean square fluctuation (RMSF), solvent accessible surface area (SASA) and radius of gyration (Rg) of the complexes. Three compounds - ZINC21883831 (Compound1), ZINC66132835 (Compound2) and ZINC38739608 (Compound3) have been found to be highly potential chemicals to serve as inhibitors for riboflavin synthase. While, the objectives in the experimental work are to clone, express, purify, and crystallize the riboflavin synthase in order to determine its 3-Dimensional structure. Following that, a 612 base pair nucleotide sequence encoding 203 amino acids of riboflavin synthase was cloned into the (pET-22b(+)) vector and expressed in the E. coli BL21(DE3) as a His-tag fusion protein. The vector-host combination significantly enhanced the level of the protein expression. The successfully expressed of the His-tag fusion protein was purified using Nickel Sepharose affinity chromatography followed by size exclusion chromatography. Crystals of the purified riboflavin synthase were obtained albeit of poor diffraction quality (4-6 Å). In terms of accuracy, this low resolution data will be detrimental to data interpretation for structure determination. Thus, the focus has been directed towards the improvement of the crystal quality including optimization of the crystallization conditions and manipulation of the grown crystals. A new construct with a thrombin recognition site was designed to remove the flexible C-terminal His-tag. Additionally, ion exchange chromatography was implemented as a polishing step for protein uniformity. The protein was successfully purified and crystallized for X-ray diffraction analysis. Crystal quality obtained from this new construct was improved in terms of its three dimensional shape appearance and quality of diffraction. The L. kmetyi riboflavin synthase was solved at 3.2 Å resolution and belonged to the orthorhombic space group C2221 with unit cell parameters a = 59.56, b = 130.63 and c = 202.50 Å. The calculated Matthews coefficient (VM) was 2.94 Å3Da-1 with a solvent content of 58.24 % and three molecules present in the asymmetric unit. Herein, this study employed computational approach as well as x ray crystallography in order to determine potential inhibitors towards riboflavin synthase. The 3D structural insights gained into riboflavin synthase are excellent as a promising starting points for the rational designs of new effective and safe anti-microbial drugs.